2019
DOI: 10.1016/j.geoderma.2019.113902
|View full text |Cite
|
Sign up to set email alerts
|

Soil stabilisation by water repellency under no-till management for soils with contrasting mineralogy and carbon quality

Abstract: No-till soil management is common around the globe, but the impacts on soil structural quality varies depending on cropping practice and inherent soil properties. This study explored water repellency as a driver of soil stabilization, as affected by soil mineralogy, granulometry and organic carbon quality in three Mollisols and one Vertisol under no-till management and with different levels of cropping intensity. The studied soils were located along a west-east textural gradient in the northern part of the Pam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
51
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(69 citation statements)
references
References 81 publications
9
51
0
9
Order By: Relevance
“…In general, hydrophobic rather than hydrophilic components of OM are assumed to improve aggregate stability (Piccolo and Mbagwu, 1999;Chenu and Cosentino, 2011;Kraemer et al, 2019). Especially in the case of water-stable microaggregates (as in our study), a relation between the wettability and microaggregation could be expected.…”
Section: Do Eps-saccharide Contents Influence Soil Microaggregation -mentioning
confidence: 57%
See 1 more Smart Citation
“…In general, hydrophobic rather than hydrophilic components of OM are assumed to improve aggregate stability (Piccolo and Mbagwu, 1999;Chenu and Cosentino, 2011;Kraemer et al, 2019). Especially in the case of water-stable microaggregates (as in our study), a relation between the wettability and microaggregation could be expected.…”
Section: Do Eps-saccharide Contents Influence Soil Microaggregation -mentioning
confidence: 57%
“…Flemming and Wuertz (2019) estimated that about 80% of soil prokaryotes live in biofilms. Furthermore, the nature of the binding factors plays an important role in the overall aggregate stability strength, since hydrophobic rather than hydrophilic components of OM improve aggregate stability (Piccolo and Mbagwu, 1999;Chenu and Cosentino, 2011;Kraemer et al, 2019). By the properties of the bonds between the units of an aggregate, it can be assumed that with decreasing diameter of the aggregates, the stability increases.…”
Section: Introductionmentioning
confidence: 99%
“…Hallett et al (2001) and Cosentino et al (2010) found that SWR was mainly controlled by hydrophobic compounds rather than pore structure when they used ethanol sorptivity as an indirect indicator of pore structure. However, other researchers have reported that SWR, when measured by the WDPT method, was more affected by pore structure than hydrophobicity (Behrends et al, 2019). However, these conclusions were not based on the direct measurement of pore structure and their results were only obtained from indirect indicators associated with pore structure.…”
mentioning
confidence: 93%
“…Microbial biomass carbon (MBC) can have a more useful and sensitive response to soil processes than the SOC (Sparling, 1992). It has been previously shown that there is a positive correlation between SWR and soluble carbohydrates linked to biological activity in soil (Behrends et al, 2019;Wander, 2004). Seaton et al (2019) also found that soil microbial community composition strongly influenced SWR that could be induced by microbes in a shorter time.…”
mentioning
confidence: 99%
See 1 more Smart Citation